JOHNNY BRAVO IN: JOHNNY BRAVO AND THE CARNIVALIZED MALE (PERcursos Linguísticos, 2020)
This article intends to analyze, based on Dialogical Discourse Analysis, the character of the animated television series Johnny Bravo as a carnivalized ideological sign of male representations. For the basis of this proposal, the notion of sign will be examined as a reflection and refraction of the social environment that creates it, and ideology, as a cultural, economic and social group that can refer both to the dominant class (official ideology) or the oppressed one (unofficial ideology),given that the ideology is a carnivalization mechanism.The objects of analysis refer to the 13 episodes of the animation first season. The methodology used was the protagonist's identity defining traits repetition stablished by observing the protagonist’s interaction with other subjects, as well as society recurring statement dialogues that reverberate the social voice of the animation character. In this sense, collation as a methodological procedure boosted the reflection of this writing and was made from publications of men and for men, in the media (magazines and Facebook, from 2010 to 2020). This article is justified by the relevance of art and media as criticism, in a dialectical-dialogical process. The intended result is a critique towards certain ridiculed representations of masculinity that reinforce toxic stereotypes and spread sexism.